Arachidonic acid and DHA status in pregnant women is not associated with cognitive performance of their children at 4 or 6–7 years. Issue 12 (8th May 2018) - Crozier, Sarah R.; Sibbons, Charlene M.; Fisk, Helena L.; Godfrey, Keith M.; Calder, Philip C.; Gale, Catharine R.; Robinson, Sian M.; Inskip, Hazel M.; Baird, Janis; Harvey, Nicholas C.; Cooper, Cyrus; Burdge, Graham C.
Abstract: Arachidonic acid (ARA) and DHA, supplied primarily from the mother, are required for early development of the central nervous system. Thus, variations in maternal ARA or DHA status may modify neurocognitive development. We investigated the relationship between maternal ARA and DHA status in early (11·7 weeks) or late (34·5 weeks) pregnancy on neurocognitive function at the age of 4 years or 6–7 years in 724 mother–child pairs from the Southampton Women's Survey cohort. Plasma phosphatidylcholine fatty acid composition was measured in early and late pregnancy. ARA concentration in early pregnancy predicted 13 % of the variation in ARA concentration in late pregnancy ( β =0·36, P <0·001). DHA concentration in early pregnancy predicted 21 % of the variation in DHA concentration in late pregnancy ( β =0·46, P <0·001). Children's cognitive function at the age of 4 years was assessed by the Wechsler Preschool and Primary Scale of Intelligence and at the age of 6–7 years by the Wechsler Abbreviated Scale of Intelligence. Executive function at the age of 6–7 years was assessed using elements of the Cambridge Neuropsychological Test Automated Battery. Neither DHA nor ARA concentrations in early or late pregnancy were associated significantly with neurocognitive function in children at the age of 4 years or the age of 6–7 years. These findings suggest that ARA and DHA status during pregnancy in the range found in this cohort are unlikely to have major influences on neurocognitive function in healthy children.